Miringoplasti tandur lemak autologus: alternatif pilihan miringoplasti di poliklinik - Harim Priyono; Dini Widiarni; Afrina Yanti (PERHATI-KL, 2011)
Background : The most common material used for the closure of tympanic membrane perforation istemporalis fascia. However, for a dry, small central perforation, the adipose tissue is a good alternative. Moreover, fat myringoplasty can be performed as an office based procedure in adult patients. Purpose:This paper will discuss the use of adipose tissue for the closure of dry, small perforations of the tympanicmembrane. Cases: A series of cases with tympanic membrane central perforation, three adult patientswith small perforations and one patient with large perforation, underwent fat autograft myringoplasty.The adipose tissue was harvested from the patients’ ear lobe. All of the patients were given decongestan,systemic and topical antibiotics as medication. Follow-ups were performed at seven days, two weeks,and one month after the procedure. Pure tone audiometry was conducted before and one month afterthe procedure. The result showed all of the patients had improvement on hearing function and no post surgical infection. Conclusion: Fat autograft myringoplasty was conducted as an outpatient clinic procedure with high success rates. This procedure can be performed under local analgesia that causingminimal discomfort. Proper patient selection making it a cost-effective procedure for an alternative ofmyringoplasty. Keywords: myringoplasty, tympanic membrane perforations, fat autograft Abstrak : Latar belakang: Jaringan yang digunakan untuk menutup perforasi membran timpani biasanyadipilih fasia temporalis. Akan tetapi, untuk perforasi yang berukuran kecil dan tidak terdapat sekret,jaringan lemak dapat digunakan sebagai bahan alternatif. Keuntungan prosedur miringoplasti denganmenggunakan jaringan lemak ini dapat dilakukan di poliklinik pada pasien dewasa. Tujuan: Makalahini akan membahas tentang kegunaan jaringan lemak untuk menutup perforasi membran timpani yangberukuran kecil dan tidak terdapat sekret. Kasus: Serial kasus empat pasien dewasa dengan perforasisentral membran timpani, tiga orang dengan perforasi kecil dan satu orang dengan perforasi luas.Penatalakasanaan: Semua pasien menjalani miringoplasti dalam analgesi lokal menggunakan tandurlemak autologus daun telinga. Keempat pasien mendapatkan terapi medikamentosa dekongestan oral,antibiotika sistemik dan topikal. Evaluasi dilakukan pada tujuh hari, dua minggu, dan satu bulan setelahprosedur dilakukan.Audiometri nada murni dilakukan sebelum dan satu bulan setelah prosedur dilakukan.Hasil audiometri menunjukkan perbaikan fungsi pendengaran pada keempat pasien dan tidak didapatkan infeksi pasca operasi. Kesimpulan: Miringoplasti tandur lemak autologus dapat dilakukan di poliklinikdalam analgesi lokal dengan tingkat kesuksesan yang tinggi dan hanya menimbulkan rasa sedikit tidaknyaman bagi pasien. Pemilihan pasien yang tepat menjadikan prosedur ini sebagai salah satu teknikalternatif miringoplasti. Kata kunci: miringoplasti, tandur lemak autologus, perforasi membran timpani